Mechanical, Tribological, and Thermal Properties of Hot‐Pressed ZrB2‐B4C Composite. (28th July 2014) - Chakraborty, Shirshendu; Debnath, Debashish; Mallick, Azizur Rahaman; Das, Probal Kumar
Abstract : The effect of addition of submicrometer‐sized B4 C (5, 10 and 15 wt%) on microstructure, phase composition, hardness, fracture toughness, scratch resistance, wear resistance, and thermal behavior of hot‐pressed ZrB2 ‐B4 C composites is reported. ZrB2 ‐B4 C (10 wt%) composite has VH 1 of 20.81 GPa and fracture toughness of 3.93 at 1 kgf, scratch resistance coefficient of 0.40, wear resistance coefficient of 0.01, and ware rate of 0.49 × 10 −3 mm 3 /Nm at 10N. Crack deflection by homogeneously dispersed submicrometer‐sized B4 C in ZrB2 matrix can improve the mechanical and tribological properties. Thermal conductivity of ZrB2 ‐B4 C composites varied from 70.13 to 45.30 W/m K between 100°C and 1000°C which is encouraging for making ultra‐high temperature ceramics (UHTC) component.